A quality analysis of thyroid cancer videos available on TikTok - Wang, Li; Li, Yongjin; Gu, Jiali; Xiao, Li (Frontiers in Public Health, 2023)
Background Thyroid cancer (TC) is becoming an increasing public health problem worldwide. TikTok is a global video-sharing social media app, which can be a source of information on TC. However, the information quality of these videos remains unknown. Methods A search of TikTok was performed with the term “甲状腺癌”and “甲状腺肿瘤” (“thyroid cancer” and “thyroid neoplasm” in Chinese). Videos included were independently assessed using six predefined questions for content scores and DISCERN scale for information quality, while the video popularity index (VPI) was also calculated. A correlation analysis was performed among duration, presence of animation, VPI, DISCERN scores, and content scores. Results A total of 56 videos were finally included, of which 49 were uploaded by physicians, 4 by health organizations, and 3 by hospitals. While 43 were real content videos, 13 were animated. The mean of DISCERN score and content score was 3.44 ± 0.72 and 5.19 ± 0.95, respectively. Good consistency was found between the two reviewers in terms of both DISCERN scores and content scores. The video duration and presence of animation were positively correlated with VPI, while DISCERN scores and content scores were not correlated with VPI. Conclusion The overall quality of TC-related videos was satisfactory, although the quality varies greatly depending on the type of source. Patients should be cautious when using TikTok as a source of TC-related information.